Research on the lubrication performance of engine piston skirt–cylinder liner frictional pair considering lubricating oil transport. (April 2020) - Sun, Jun; Hao, Feifei; Liu, Guangsheng; Wang, Hu; Teng, Qin; Miao, Enming; Zhao, Xiaoyong; Ren, Yanping; Zhu, Guixiang
In current lubrication analysis of piston skirt, the flooded status is generally considered in the piston skirt–cylinder liner frictional pair in all strokes of an engine operating cycle. However, the quantity of lubricating oil at the entrance of piston skirt cannot always ensure the sufficient lubrication status of piston skirt–cylinder liner frictional pair when the piston moves from the bottom dead center to the top dead center in actual engine. In this article, based on the model of piston secondary motion, fluid lubrication, and lubricating oil flow, the lubrication performance of piston skirt–cylinder liner frictional pair is analyzed, in which the quantity of lubricating oil detained on the surface of cylinder liner after the piston skirt moves from the top dead center to the bottom dead center and is considered as the quantity of lubricating oil at entrance of piston skirt when the piston moves from the bottom dead center to the top dead center. The results show that compared with current analysis, in which the sufficient lubrication of piston skirt–cylinder liner frictional pair is assumed in all strokes of engine, there are remarkable changes for the lubrication performance of piston skirt–cylinder liner frictional pair and the piston secondary motion when the lubrication status of the frictional pair in the upstroke of piston is determined by considering actual lubricating oil transport in the lubrication analysis of piston skirt.